Post-exercise cognitive testing to assess persisting alterations in athletes with a history of concussion. (3rd July 2021) - Sicard, Veronik; Caron, Gabriel; Moore, Robert Davis; Ellemberg, Dave
ABSTRACT: Primary Objective : To determine whether a physical exercise protocol could reveal persistent cognitive alterations in university athletes with a history of concussion (HOC). Thirty-four HOC and 34 controls participated in this study. Research Design : Cross-sectional. Methods and Procedures : The exercise protocol consisted of a 20-min bout on a stationary bike at 80% of the theoretical maximal heart rate. Before and after the exercise, participants performed a computerized switch task designed specifically to recruit executive functions. Group × Condition (pre- and post-exercise) repeated measures of ANCOVAs for accuracy, reaction time, and inverse efficiency score on the switch task were conducted. Chi-square tests were run to determine if the proportion of HOC and controls who underperformed (at least 2SD lower than the control group's average score) at rest and post-exercise were similar. Whilst no interaction or main effects were found with ANCOVAs, significantly more HOC athletes (21%) underperformed following exercise than at rest (3%) on the switch task, p = .02. The current results indicate that an acute bout of exercise can reveal persistent alterations that are not present at rest in the protracted phase of concussion. They also highlight the importance of considering inter-individual differences in recovery trajectories.